PROYECTO DE INVERSION PARA LA IMPLEMENTACION DE UNA EMPRESA DE SERVICIO DE LAVADO Y SECADO DE ROPA CASUAL EN LA PARROQUIA DE ZAMORA DEL CANTON ZAMORA DE LA PROVINCIA ZAMORA CHINCIPE - Cango Mora, Lourdes Ayde (2016)
This project aims to help economic development by implementing a company dedicated to providing service laundry and drying casual clothing in the parish of Zamora Canton Zamora, with the aim of delivering a new service to the community and get profitability. This entrepreneurial initiative is aimed for those who generate income, ie the economically active population. methodologies and techniques that were useful in determining the sample or number of surveys to be applied in the parish was used in the preparation of this project, the same as were 377. In addition a market study which was carried out, the total population is 6,654 people, of whom a potential 2302 people there are journeying to determine the real demand giving a total of 2003 people and an effective demand for 1,722 people demand was determined allowing us to determine an unmet demand 152,135 kilos of clothes. In the technical study the size of the project where the company will have an installed capacity of 24,192 kilos of linen capacity was determined, and will start its activities with a capacity utilization of 16,934 kilos working 8 hours a day for 252 working days, its location will be in the streets Diego Cow between May 24 and Pio Jaramillo and its distribution will be made in an area of 56m2.